2017
DOI: 10.1051/epjconf/201716102029
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond filamentation of optical vortex in a medium with anomalous group velocity dispersion

Abstract: Abstract. Within the framework of the slowly varying wave approximation method, the pictures of spatio-temporal dynamics of femtosecond pulse in a ring beam with phase singularity were obtained during propagation in CaF2 crystal with anomalous group velocity dispersion. We show formation of tubular structure of the beam and explain reasons of its appearance. Fluence and linear plasma concentration dependencies on propagation distance are analyzed.Filamentation of laser radiation is a phenomenon of formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It is shown that optical vortex in a medium with normal group velocity dispersion forms a filament of tubular shape with a radius of several microns, whereas in an annular beam without phase dislocation, the filament is formed on the axis. Analysis of the formation of the tubular structure of the optical vortex, spatial distribution of the fluence and plasma concentration under the conditions of AGVD was performed in [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that optical vortex in a medium with normal group velocity dispersion forms a filament of tubular shape with a radius of several microns, whereas in an annular beam without phase dislocation, the filament is formed on the axis. Analysis of the formation of the tubular structure of the optical vortex, spatial distribution of the fluence and plasma concentration under the conditions of AGVD was performed in [15].…”
Section: Introductionmentioning
confidence: 99%